Distal Posterior Cerebral Artery Ruptured Aneurysm: A Rare Case Report and Review of Literature - Kasapas, Konstantinos; Malli, Antonia; Charitos, Dimitrios; Georgakoulias, Nikolaos (Asian Journal of Neurosurgery, 2022)
Distal posterior cerebral artery aneurysms consist of a rare vascular entity whose treatment approach remains challenging. Few studies exist scarcely in the literature reporting cases of P4 ruptured aneurysms. In this study, we present the case of a 49-year-old female patient who was admitted to our Neurosurgery Department with the World Federation of Neurological Surgeons grade IV, Fischer grade IV subarachnoid hemorrhage due to a right distal posterior cerebral artery aneurysm. She successfully underwent surgery via a posterior occipital interhemispheric approach. The patient recovered well from surgery, and the following days, she was successfully extubated and had a significant neurological improvement. However, she died during her rehabilitation due to sepsis and severe acute respiratory distress syndrome.
Keywords: posterior cerebral artery; ruptured distal PCA aneurysm; clipping; subarachnoid hemorrhage